(untitled) (Beacon: International Journal of Education and Social Studies, 2025)
This study examines the influence of entrepreneurial self-efficacy on improvisational behavior in private higher education organizations. In an increasingly dynamic and competitive educational environment, leaders are required to adapt quickly and make effective decisions in response to uncertainty and rapid change. Entrepreneurial self-efficacy refers to an individual’s belief in their ability to successfully perform entrepreneurial tasks, while improvisational behavior reflects the capacity to develop and implement spontaneous actions when facing unexpected situations. Using a quantitative survey approach, data were collected from leaders and administrators of private higher education institutions. Entrepreneurial self-efficacy was measured through five dimensions: entrepreneurial creativity, planning ability, resource organization, ambiguity management, and financial knowledge. Improvisational behavior was assessed through innovation, proactiveness, and risk-taking. The findings indicate that entrepreneurial self-efficacy has a positive and significant effect on improvisational behavior. All dimensions of entrepreneurial self-efficacy contribute to enhancing improvisational behavior, with ambiguity management and entrepreneurial creativity emerging as the strongest predictors. These results highlight the importance of entrepreneurial self-efficacy as a strategic leadership competency that promotes adaptability, innovation, and responsiveness in private higher education organizations.